A sociedade 5.0 e o novo balizamento normativo das relações de trabalho no plano das empresas - Medeiros, Breno (2022)
This doctoral thesis addresses the evolutionary aspects of society 5.0 in the field of work, focusing on the theoretical emulation of the concept of human dignity in the 5.0 workplace. The investigation begins with an outline of the historical evolution of industrial revolutions, up to revolution 4.0, when the society's socio-environmental sustainability agenda 5.0 emerges as an ethical-conforming paradigm of labor relations, means of production and consumption habits. In the second part, the concept of dual dignitary dimension of work 5.0 is developed, which encompasses the “4S” level of compromising dignity (support, status, health, and safety) and points out to emancipatory dignity (freedom to work with the right of career self-management and unlimited earning potential) as an innovation of society's creative work environment 5.0. Finally, pragmatic issues of jurisdiction in conflicts within the scope of labor relations 5.0 are examined whenever the labor nature of these new relations is established as a prerequisite for legislative intervention, via constitutional amendment. This is so, in order to set forth the jurisdiction to process these lawsuits in the Labor Court, as well as the conflicts of jurisdiction arising therefrom